Observing Digital Leadership Model through Interpretative Phenomenological Analysis a la Regulator during Pandemic Era - Ridhony Marisson Hasudungan Hutasoit; Florentina Kurniasari; Ringkar Situmorang (Indonesian Journal of Multidisciplinary Science, 2022)
he COVID-19 pandemic has had a significant impact on changing people's behavior. The pandemic has become one of the accelerators for the acceleration of human civilization to internalize technology in various dynamics of human life. One of the sectors affected by this pandemic is the financial services sector, which includes the banking sector, capital markets, and the non-bank financial industry. This dynamic needs to be responded by the Financial Services Authority (OJK) as the regulator, supervisor, and enforcer and consumer protection service in the financial services sector in accordance with Law Number 21 of 2011 concerning the Financial Services Authority. The role of OJK representatives in the regions became significant as an extension of the head office. The role of digital leaders is needed in achieving task force performance through digital transformation. The phenomenological approach is an option in this research as a medium to explore research problems. Researchers use Interpretative Phenomenological Analysis (IPA) as a data analysis technique in tracing the meaning of the phenomenon that occurs. Based on the results of research conducted by the OJK of Southeast Sulawesi Province, seven qualities of the digital leader model in the success of digital transformation consisted of digital literacy, vision, stakeholder concern, agility, risk taking, collaboration, and compliance with regulations/policies.